Physico Chemical Changes in Soil as Influenced by Natural Tree and Grass Covers in Arid Rangeland - Sharma, B D; Bawa, A K; Gupta, I C (Annals of Arid Zone, 2016)
Studies were undertaken to ascertain changes as influenced by vegetation cover i.e. trees and grass over bare dune soil. Marked changes were observed in soil chemical pattern under vegetation cover in comparison to adjacent bare dune as organic carbon increased from 0.03% in bare dune soil to 0.4% under tree cover and 0.15% under grsss cover, total N increased from 0.007% on bare soil to 0.04% under tree and 0.01% under grass, available P increased from 7.5 kg ha-1 on bare dune soil to 17.0 kg ha-1 under tree and 9.0 kg ha-1 under grass cover and available K revealed similar pattern.Nutrient level under tree cover decreased with increase in soil depth while under grass cover nutrient decreased marginally upto 30 cm depth without further change with depth. Physical characteristics also improved marginally under tree and grass cover.